Pola Komunikasi Pasangan Nikah Muda Dalam Menjaga Keharmonisan Rumah Tangga Di Kecamatan Huristak Kabupaten Padang Lawas - Masrona Harahap; Mutiawati Mutiawati; Irma Yusriani Simamora (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
In general, this research aims to find out how young married couples communicate in maintaining household harmony in Tobing Julu village, Huristak sub-district, Padang Lawas district, what are the factors that cause young marriages in Tobing Julu village, Huristak sub-district, Padang Lawas district, how do young married couples behave? in resolving conflicts that occur within households in Tobing Julu village, Huristak sub-district, Padang Lawas district. This type of research uses qualitative methods through a descriptive approach which aims to describe information in detail according to the reality that occurs at the research location. Data was obtained through observation and interviews. Data analysis for this research uses a version of the Miles and Hermawan data model which includes data collection, data reduction, data display and conclusion drawing/verification. The results of the research show that the factors causing young marriages in Tobing Julu village, Huristak sub-district, Padang Lawas district are economic, parents and their own will, the communication patterns used by young married couples in maintaining household harmony in Tobing Julu village, Huristak sub-district, Padang Lawas district are cooperative communication patterns and defensive communication patterns and the way young married couples resolve conflicts in Tobing Julu village, Huristak sub-district, Padang Lawas district, is to communicate well, be open to each other, lower the ego of each partner and accept all forms of the partner's strengths and weaknesses.